2020
DOI: 10.1096/fj.201902946r
|View full text |Cite
|
Sign up to set email alerts
|

EDAG mediates Hsp70 nuclear localization in erythroblasts and rescues dyserythropoiesis in myelodysplastic syndrome

Abstract: During human erythroid maturation, Hsp70 translocates into the nucleus and protects GATA‐1 from caspase‐3 cleavage. Failure of Hsp70 to localize to the nucleus was found in Myelodysplastic syndrome (MDS) erythroblasts and can induce dyserythropoiesis, with arrest of maturation and death of erythroblasts. However, the mechanism of the nuclear trafficking of Hsp70 in erythroblasts remains unknown. Here, we found the hematopoietic transcriptional regulator, EDAG, to be a novel binding partner of Hsp70 that forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This hypothesis is supported by our western blot as well as RNA-seq analysis (Supplemental Figure 13A-C). It has also been reported that abnormal expression or function of HSP70 can promote ineffective erythropoiesis in β-thalassemia 43,44 , MDS 23,45 , and Diamond-Blackfan anemia (DBA) 24,46 . In addition, an increasing number of studies have revealed other functions of HSP70 chaperone proteins and linked the methylation of non-histone proteins to the regulation of gene transcription 33,47 .…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by our western blot as well as RNA-seq analysis (Supplemental Figure 13A-C). It has also been reported that abnormal expression or function of HSP70 can promote ineffective erythropoiesis in β-thalassemia 43,44 , MDS 23,45 , and Diamond-Blackfan anemia (DBA) 24,46 . In addition, an increasing number of studies have revealed other functions of HSP70 chaperone proteins and linked the methylation of non-histone proteins to the regulation of gene transcription 33,47 .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that Hemgn deletion accelerates HSPCs response to IFN‐ γ via suppressing TC45 activity. Given that Hemgn deficiency does not alter TC45 expression and HEMGN can interact with a variety of nuclear proteins, [ 14 , 15 , 48 ] the investigation of interactions between HEMGN and Stat1/TC45 may help to explain the exact mechanism by which HEMGN regulates TC45‐medicated Stat1 dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The transient activation of cysteine aspartate specific protease-3 (Caspase-3) is necessary for erythroblasts maturation, and GATA-1 is also essential for the maturation of erythroblasts ( Dong et al, 2020 ). In the terminal stage of normal erythroid cells differentiation and maturation, Heat shock protein 70 (HSP70) is translocated from the cytoplasm into the nucleus, and it can serve as a chaperone protein within the nucleus to shield the GATA-1 from being cleaved by Caspase-3 ( Ribeil et al, 2007 ; Arlet et al, 2014 ).…”
Section: Ie In β-Thalmentioning
confidence: 99%